Sambladuras em tesouras de madeira tipo Howe - Renata Braga de Albuquerque (2006)
This paper has for objective to supply to practical and theoretical contributions the correct detailing of the joints of shears with wooden structure of the type Howe, covered for ceramic roofing tiles being successful vain up to 12 meters. Amongst the existing joints, it was chosen for analysis - for the great use in the country, for constructivesimplicity and the low cost - the called sambladura, or has carved, that it has the characteristic not to use no type of bolt (metallic, wooden, or another one) to resist the operating efforts. In the sambladuras, the cuts made in the parts for rabbet ones in the others can compromise the functioning of all the structure. Efforts of shear, compression and traction, usually gifts in these types of joints can take the structure to the collapse. Being thus stages of bibliographical research and field had been carriedthrough in this research in order to present existing problems in the construction of this type of joints throughout history. Through the bibliographical research constructive solutions for each one of the analyzed joints are presented, that depend, in turn, of a correct sizing. The stage of field was initiated with election of the constructions (old andrecent) that they had served of model for the verification of the joints. The joints had been verified how much to the height of the tooth, how much to the necessary recess to the shear and how much to the displacement of pontalete (or central vertical bar), using NBR 790/97 in relation to the employed values of resistance. Also factors had been cited that influence the parts of structures wooden: the humidity, the wooden type and the structural integrity. It can be concluded that the majority of the inspected joints had been constructed of incorrect form in relation to the sizing used currently - in the totality of the analyzed aspects - independently of the date of construction of the constructions (historical aspect), printing some indifference with this type of joints in the structures of this transport